Behavior of Generation Z, Obesity, and Chronic Kidney Disease among Children and Adolescents: A Literature Review - Al Furqon; Rasyid Ridha (Talenta Publisher, 2026)
Background: Generation Z is defined as individuals born between 1995 and 2010. Being raised in digital era, some lifestyle of Generation Z in nutritional fullfillment and physical activity raises concern about obesity and chronic kidney disease (CKD). Objectives: This review looked into role of behavior in obesity and chronic kidney disease in Generation Z. Methods: Search strategy was done using keywords, such as “obesity”, “chronic kidney disease”, “children”, “adolescent”, and “generation Z” in several search engines, including Pubmed, ScienceDirect, and Google Scholar. Discussion: Ease of digital access, including instant meal order, makes Generation Z tend to have high calorie food intake, but with minimal physical activity. The imbalance of daily energy expenditure contributes to obesity. Obesity consequently triggers neurohormonal pathways leading to chronic kidney damage. Conclusion: Preventive measures should be taken, including healthy eating habits, daily water intake, and engaging in more physical activity. Keyword: adolescent, children, chronic kidney disease, generation Z, obesity Background: Generasi Z adalah individu yang lahir antara tahun 1995 hingga 2010. Hidup berkembang dalam era perkembangan digital, gaya hidup Generasi Z terutama yang berkaitan dengan asupan nutrisi dan aktivitas fisik meningkatkan risiko terjadinya obesitas dan penyakit ginjal kronik. Objectives: Tinjauan pustaka ini menelaah peran gaya hidup dan perilaku terhadap terjadinya obesitas dan penyakit ginjal kronik pada Generasi Z. Methods: Telaah literatur dilakukan menggunakan kata kunci, “obesitas”, “penyakit ginjal kronik”, “anak”, “remaja”, dan “generasi Z” melalui mesin pencari, seperti Pubmed, ScienceDirect, dan Google Scholar. Discussion: Generasi Z cenderung memanfaatkan kemudahan akses digital, termasuk dalam mendapatkan makanan sehari-hari. Hal ini umumnya menyebabkan asupan kalori berlebih dengan aktivitas fisik yang minimal. Ketidakseimbangan tersebut menjadi penyebab utama obesitas, yang kemudian dapat merangsang mekanisme neurohormal tubuh yang berakhir pada kerusakan ginjal kronik. Conclusion: Pencegahan obesitas dan penyakit ginjal kronik, seharusnya dapat dilakukan dengan melaksanakan pola makan yang sehat, asupan air yang cukup, dan meningkatkan aktivitas fisik. Keyword: anak, generasi Z, obesitas, penyakit ginjal kronik, remaja